2019
DOI: 10.3390/molecules24010147
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasonic-Microwave Assisted Extraction and Hepatoprotective Activities of Polysaccharides from Trametes orientalis

Abstract: Ultrasonic-microwave assisted extraction (UMAE) of Trametes orientalis polysaccharides was optimized by response surface methodology. Hepatoprotective effects of a purified T. orientalis polysaccharide (TOP-2) were evaluated by alcohol-induced liver injury model mice. The optimal UMAE parameters were indicated as below: ratio of water to raw material 28 mL/g, microwave power 114 W, extraction time 11 min. The polysaccharides yield was 7.52 ± 0.12%, which was well consistent with the predicted value of 7.54%. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Transaminases are rapidly released into blood stream when injuries or diseases affected the body tissues [ 34 ]. The results of the present study unveiled that the levels of AST, ALT, and ALP in the mouse model of acute alcoholic liver injury were significantly increased in serum, which is consistent with findings of previous reports [ 35 ]. This indicated that the mouse model of acute alcoholic liver injury was successfully established.…”
Section: Discussionsupporting
confidence: 93%
“…Transaminases are rapidly released into blood stream when injuries or diseases affected the body tissues [ 34 ]. The results of the present study unveiled that the levels of AST, ALT, and ALP in the mouse model of acute alcoholic liver injury were significantly increased in serum, which is consistent with findings of previous reports [ 35 ]. This indicated that the mouse model of acute alcoholic liver injury was successfully established.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the bioactivity of polysaccharides with 3D conformation is higher than those without a 3D structure. [26] Therefore, this result suggested that GFP-1-a and GFP-2-a are potentially bioactive polysaccharides.…”
Section: Conformational Resultsmentioning
confidence: 81%
“…As shown in Figure 1a, the best liquid-material ratio was 30 mL g -1 . The polysaccharide in G. frondosa could not be completely extracted when the liquid-material ratio was low, [26] but if the liquid-material ratio was too high the yield would not be increased but the process would be wasteful of energy and materials, and more acetone would also be consumed in subsequent treatment.…”
Section: Influence Of Raw Materials Extraction Process On Polysaccharide Yieldmentioning
confidence: 99%
“…The yield of BS mucilage increased with increasing extraction time and an increasing liquid–solid ratio, but the yield then decreased as these two variables increased further. The response surface slope of the interaction between the extraction time and liquid–solid ratio was steep and the contour plot was elliptical, which suggested that the interaction between the two variables was extremely significant [29]. Figure 1E evaluates the effect of the shear speed and liquid–solid ratio on the yield of BS mucilage.…”
Section: Resultsmentioning
confidence: 99%